Characterization of graphene based capacitive microphone - Haslinawati Mohd Mustapha; M.F. Mohd Razip Wee; Ahmad Rifqi Md Zain; Mohd Ambri Mohamed (Penerbit Universiti Kebangsaan Malaysia, 2019)
This research focuses on the design, fabrication and characterization of the graphene based capacitive microphone. Finite element analysis (FEA) is first simulated in order to design and study the proposed graphene based capacitive microphone. While the fabrication introduced MEMS technique in order to reduce the physical size, volume and cost without neglecting the performance. This study discusses on physical characteristics of graphene diaphragm for capacitive microphone. The fabrication of 200 nm air gap and the free-standing suspended graphene with the contribution of the van der Waals force between the graphene layer as a diaphragm and the substrate are presented in this study. The first stage involved in this study was the photolithography process of patterning electrodes with 4 different dimensions of diaphragm. The characterization was performed by using surface profilometer, optical microscopy, Raman spectroscopy and FESEM to evaluate the physical characteristics of the diaphragm. In the last stage, LCR meter was used to measure the capacitive change with different diameter of graphene diaphragm within frequency range of 20 Hz to 20 kHz. FEA analysis showed the good sensitivity against the frequency response for the largest proposed diameter of diaphragm.